Fabrication of three-dimensional honeycomb structure for aeronautical applications using selective laser melting: a preliminary investigation. Issue 6 (20th October 2014) - Chantarapanich, Nattapon; Laohaprapanon, Apinya; Wisutmethangoon, Sirikul; Jiamwatthanachai, Pongnarin; Chalermkarnnon, Prasert; Sucharitpwatskul, Sedthawatt; Puttawibul, Puttisak; Sitthiseripratip, Kriskrai
Abstract : Purpose: – The purpose of this paper was to investigate the feasibility on design and production of a three-dimensional honeycomb based on selective laser melting (SLM) technique for use in aeronautical application. Design/methodology/approach: – Various polyhedrons were investigated using their mechanical property, i.e. strain energy density (SED), by means of finite element (FE) analysis for the suitability of use in aerospace application; the highest SED polyhedron was selected as a candidate polyhedron. From the FE analysis, the truncated octahedron (three-dimensional honeycomb) structure was considered to be the potential candidate. Polyhedron size and beam thickness of the open-cellular three-dimensional honeycomb structure were modelled and analysed to observe how the geometric properties influence the stiffness of the structure. One selected model of open-cellular honeycomb (unit cell size: 2.5 mm and beam thickness: 0.15 mm) was fabricated using SLM. The SLM prototypes were assessed by their mechanical properties, including compressive strength, stiffness and strength per weight ratio. To investigate the feasibility in production of airfoil section sandwich structure, NACA 0016 airfoil section with three-dimensional honeycomb core was constructed and also fabricated using SLM. Findings: – According to the result, the three-dimensional honeycomb has elastic modulus of 63.18 MPa and compressive strength of 1.1 MPa, whereas strength per weight ratio is approximately 5.0 × 103 Nm/kg. The FE result presented good agreement to the mechanical testing result. The geometric parameter of the three-dimensional honeycomb structure influences the stiffness, especially the beam thickness, i.e. increase of beam thickness obviously produces the stiffer structure. In addition, the sandwich structure of airfoil was also successfully manufactured. Originality/value: – This work demonstrated the production of sandwich structure of airfoil using SLM for aeronautical engineering. This investigation has shown the potential applications of the three-dimensional structure, e.g. aircraft interior compartment components and structure of unmanned aerial vehicles.